2014
DOI: 10.1097/anc.0000000000000117
|View full text |Cite
|
Sign up to set email alerts
|

The Neonatal Nurse's Role in Preventing Abusive Head Trauma

Abstract: Background Abusive head trauma in infants occurs in 24.6 to 39.8 per 100,000 infants in developed countries. Abusive head trauma refers to any type of intentional head trauma an infant sustains, as a result of an injury to the skull or intracranial contents from a blunt force and/or violent shaking. Clinical Question What evidence-based interventions have been implemented by neonatal nurses to prevent abusive head trauma in infants? Search Strategy: PubMed was search to obtain English language publications f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
0
2
0
11
Order By: Relevance
“…Erkek bebek, çoğul gebelik, erken doğan bebekler, düşük doğum ağırlığına sahip bebekler, bakıcı ile bebek arasındaki ilişkinin zayıf olması SBS için risk etmenlerindendir (2,7,25) . Çalışmamızda, bebeklerin gestasyon haftaları ve uyku düzenleri ile annelerin bebeklerini sarsmayı düşünme durumlarını etkilemez iken, bebeklerin cinsiyeti ile annelerin bebeklerini sarsma durumları arasında istatistiksel olarak anlamlılık belirlenmiş olup, erkek bebeklerin daha çok sarsıldığı saptandı (p<0.05).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Erkek bebek, çoğul gebelik, erken doğan bebekler, düşük doğum ağırlığına sahip bebekler, bakıcı ile bebek arasındaki ilişkinin zayıf olması SBS için risk etmenlerindendir (2,7,25) . Çalışmamızda, bebeklerin gestasyon haftaları ve uyku düzenleri ile annelerin bebeklerini sarsmayı düşünme durumlarını etkilemez iken, bebeklerin cinsiyeti ile annelerin bebeklerini sarsma durumları arasında istatistiksel olarak anlamlılık belirlenmiş olup, erkek bebeklerin daha çok sarsıldığı saptandı (p<0.05).…”
Section: Discussionunclassified
“…Sarsılmış bebek sendromu, istismara bağlı çocuk ölümlerinin ya da yaşamı tehdit edici sonuçların %95'inden sorumlu olup, sıklıkla 2 yaş altındaki bebeklerde rastlanmakla birlikte, 5 yaşa kadar görülebilmektedir (6)(7)(8) . SBS sıklığı kesin olmamakla birlikte, bir yaş altında 21-24,6/100,000 oranında bildirilmekte ve bebeklerinin çoğunun 6 aydan ufak olduğu belirtilmektedir (6) .…”
Section: Introductionunclassified
“…Aurrez aipatu bezala, Haur Astinduaren Sindromea osasun publikoko arazo larri bat da. Arlo ezberdinetan eragin eta hainbat ondorio sortzen ditu (CDC, 2010;CDC, 2013;Allen, 2014;Barr, 2014).…”
Section: Momentuko Egoeraunclassified
“…Haurrei dagokienez, euren garapen fisiko, sozial eta psikologikoan izaten du eragina. Gaitz konplexua eta aldakortasun handikoa izanik, astinduak izan diren haurrez gain euren familietan ere, maila ezberdinetan, ekonomikoan, psikologikoan etab.ean eragin eta inpaktu handia sortzen duela adierazten den arren, ez da ondorio hauek zeintzuk diren ebidentzian jartzen duen informazio zehatzik (CDC, 2010;Allen, 2014;Barr, 2014) .…”
Section: Ikergazte 2017 Osasunaunclassified
“…Research has shown that prolonged, intractable crying is a risk indicator for stress and, consequently, for shaken baby syndrome. Education programs that teach parents/carers that shaking a baby is dangerous and alerts them to time frames where infants may be prone to unsettled behaviors and strategies to manage that have proven effective and are a good example of a universal service (Allen, 2014). Medical general practitioners (GPs), maternal and child health nurses, and social media can also be vital tools and sources of information for new parents.…”
Section: Applying Haddon’s Matrix To a Public Health Child Protection Modelmentioning
confidence: 99%